In Technogenic and Environmental Emergencies Specific Aspects of Protecting the Population (Eurasian Research Bulletin, 2023)
It is known that emergency situations are an unprotected process that can happen in every country and every place. It is important to prepare the population in advance for such situations. This article discusses preventive measures to protect the population from such situations.